Social encouragement can influence manual preference in 6 month-old-infants - Morange-Majoux, Françoise; Devouche, Emmanuel (Frontiers in Psychology, 2014)
The purpose of this study was to investigate the influence of social encouragement on infants’ hand movements, in particular on manual preference. Thirty-six infants were observed at 5.5 months. In a first step, their spontaneous manual preference was recorded with an object placed at the midline position. The second step consisted in encouraging infants to use their non-preferred hand by putting the object near that hand and congratulating them. The third step was similar to the first one (object placed at the midline position) except that the infant continued to be congratulated when (s)he used the non-preferred hand for reaching the object. Results showed that half of the infants exhibited a spontaneous manual preference and that a majority of these infants could use their non-preferred hand when verbally encouraged. Moreover, infants showing a left hand preference modified their hand-use more easily than infants showing a right hand preference. Although our findings reveal only a temporary and short-term influence of the social context, results are discussed in light of a socio-cognitive perspective whereby social encouragement can model manual preference, in particular its strength and stability. Highlights • At 5.5 months, a manual preference was observed in 47.2% of the infants. • The preference for the left hand was observed in 35.3% of the infants who presented a manual preference. • Left-handers change more easily their hand-use than right handers.